Design and Analysis of The Energy Storage and Return (ESAR) Foot Prosthesis Using Finite Element Method - Alfiana Fitri Istiqomah; Rifky Ismail; Deni Fajar Fitriyana; Sulistyo Sulistyo; Akmal Putra Fardinansyah; Murti Ayu Nur Safitri; Januar Parlaungan Siregar (Center for Biomechanics, Biomaterials, Biomechantronics and Biosignal Processing (CBOIM3S), 2021)
ABSTRACT. Disability issue has increased in recent years due to the high number of accidents and vascular disease. Loss of limb function for people with amputations often results in an abnormal gait. Energy Storage And Return (ESAR) foot prostheses provide an alternative to help improve gait and minimize metabolic energy expenditure during the walking phase of amputees. This study used 3 designs with models from the Catia V5 Software. The finite element method analysis used Ansys Workbench 18.1 software to evaluate the three designs with a loading of 1.2 times the user's body weight with a maximum weight of 70 kg in normal walking activities. The simulated material is carbon fiber prepreg which has tensile strength, Young's modulus, Poisson ratio, and density of 513.72 MPa, 77.71 GPa, 0.14, and 1.37 g/cm3. The decision-making matrix method is used to determine the best foot prosthesis design according to predetermined criteria. The highest value in the decision-making matrix is 76 in Design 3. The chosen design (Design 3) after gait cycle analysis has a maximum von Mises stress value of 76.956 MPa and the safety factor value for each gait cycle heel strike loading model is 1.0762; foot flat 3.2509; toe-off 6.6263.